MENUMBUHKAN MINAT DALAM MENINGKATKAN DAN MEMPERLUAS WAWASAN PEMAHAMAN DASAR AKUNTANSI & MATEMATIKA BAGI SISWA SMA NEGERI 1 HUTABAYURAJA - Hanafi Asnan; Peranita Manurung; Salsa Citra Cantika; Mauly Mauly (Smart Education, 2024)
Abstract: Sometimes students who have academic weaknesses or low interest are afraid to choose a major that is related to mathematics. In everyone's opinion, mathematics is difficult, but our daily lives are never free from mathematics. This means managing data and finances such as accounting. Accounting is a process of recording, classifying, summarizing, processing and presenting data, transactions and events related to finance so that people who use it can easily understand it to make decisions and for other purposes. This research uses a descriptive method with a quantitative approach. The subjects in this research were students in grades 11 and 12 in the 2022-2023 class who were active and had participated in the learning process during school. The instrument in this research uses a Likert scale model questionnaire which contains a number of statements with four alternatives. From the total distribution of 30 copies of the questionnaire with a percentage of 78% so that it can be processed and explained by researchers, because it meets the sample size, the author concludes that with a response rate of 78%, it can be categorized as